Analisis Sikap dan Pengetahuan Ibu Melalui Program Home Gardening dan Penyuluhan Gizi di Desa Binaan Tenayan Raya Pekanbaru - Rini Harianti; Fajar Sari Tanberika (STIKes Hang Tuah Pekanbaru, 2015)
The utilization of home garden can support the availability of food diversity at the household level, while the variety of food pattern of family’s consumption will come true, nutritionally balanced and safety. Currently, the utilization of home garden has not been done optimally. Through utilization of home gardening and nutrition education is expected to provide sufficient added value in the food and nutrition needs of the family and be able to expand the knowledge and attitude of maternal nutrition. Therefore, to increase the utilization of home gardening is very necessary to education, guidance and provision of the necessary means. The objective of this study was to analyze the attitudes and knowledge of mothers through home gardening and nutritional education in guided village Tenayan Raya Pekanbaru. The research applied experimental design. The subjects were 100 mother, which were choosen from four village in Tenayan Raya. The results showed that: (1) educational status of mother has significant effect (p = 0.003), (2) the energy-protein consumption to family income has significant effect (p = 0.031), (3) the knowledge mothers of home gardening program with education have significant effect (p = 0.004), (4) the attitude of the mother towards the home gardening program with income and occupation status of mother each have significant effect (p = 0.035, p = 0.006), (5) analysis of the knowledge and attitude mother to education have significant effect (p = 0.024), (6) the knowledge and attitudes of the mother received nutritionaol education after the intervention have significant effect (p = 0.000).